Dental Arch Dimensions of Nigerian Children with Hypertrophied Adenoids - Vivien Ijeoma Osiatuma; Olayinka Donald Otuyemi; Kikelomo Adebanke Kolawole; Yemisi Bola Amusa; Babatunde Ogunbiyi Ogunbanjo (Galenos Yayinevi, 2017)
Objective:The study objective was to assess the effect of adenoid hypertrophy on the dental arch dimensions of children in Ile-Ife, Nigeria.Methods:Ninety patients aged 3-12 years attending the Otorhinolaryngology Clinic at Obafemi Awolowo University Teaching Hospital Ile-Ife diagnosed as having hypertrophied adenoids and 90 children from the Child Dental Health Clinic were recruited as adenoid and control subjects respectively. Arch and palatal vault dimensions, including total arch length; inter-canine, inter-premolar, and inter-molar widths; palatal length; and palatal heights measured at three levels and palatal volume were determined for both groups from dental casts.Results:Maxillary arch dimensions were shorter in the adenoid group than the control group; however, only total maxillary arch length was significantly shorter (p=0.049). Mandibular arch dimensions with the exception of inter-molar width were significantly shorter in the adenoid group (p<0.05). Adenoid subjects had significantly increased palatal heights at canine, premolar, and molar levels and reduced palatal volume compared to the control subjects (p<0.05).Conclusion:Adenoid subjects demonstrated shorter maxillary and mandibular arch dimensions compared with control subjects, with the differences being more evident in the lower arch. They also exhibited increased palatal heights at all levels and reduced palatal volume compared with control subjects.